Penggunaan Wordwall sebagai Media Evaluasi Berbasis HOTS dalam Pembelajaran Pendidikan Pancasila Kelas V Sekolah Dasar : abstract, Introduction, Theoretical Review, Results and Discussion, Conclusions, References - Alfarisi, M. Haikal; Yalvelma Miaz; Yeni Erita; Jefri Oktaviandi; Aditra Zulfi (Journal of Practice Learning and Educational Development, 2026)
The background to this research arose from the fact that teachers have not yet fully utilized the information technology (IT) available in schools. The development of innovative, engaging, and technology-based learning media is still limited, requiring teachers to improve their digital media skills to make the learning process more engaging and prevent student boredom (Prasetyo & Sari, 2021; Nugraha, 2020). Based on these challenges, this study was designed to explore the use of Wordwall as a more innovative learning evaluation tool. Furthermore, the use of Wordwall as a technology-based learning tool has not been significantly implemented in schools, despite the platform offering interactive and engaging features for students. This study aims to describe how Wordwall is used, the obstacles faced by teachers, and student responses to this platform as a tool for evaluating thematic learning for fifth-grade students at SDN 17 Pasaman. This study used a qualitative approach with a case study design, with research subjects including teachers and 25 fifth-grade students at SDN 17 Pasaman, Pasaman District, West Pasaman Regency, during the 2025/2026 academic year. Data collection was conducted through observation, interviews, questionnaires, and documentation, followed by descriptive analysis. The results showed that the use of Wordwall in the evaluation of Pancasila Education learning generated a very positive response from students. Teachers reported that students became more active and enthusiastic during the evaluation process. Quantitative findings supported this observation, with 92% of students feeling motivated to study harder, 91% encouraged to achieve a top scorer, 91% excited to solve problems, 72% challenged to answer questions quickly, and 81% encouraged to compete for the highest score. Furthermore, 97% of students stated that Wordwall was practical and enjoyable to use. The platform features an automatic assessment feature that facilitates teacher correction, allows for the creation of game-based evaluations without requiring programming skills, and can be tailored to the learning material (Putra, 2022; Suryani, 2020). This indicates that Wordwall can increase student motivation while providing an interactive, creative, and enjoyable learning experience.